Coping with problems that flaw the estimate of mammography sensitivity in population-based screening programmes: the Italian perspective. (July 2016) - Ravaioli, A.; Mancini, S.; Naldoni, C.; Falcini, F.; Ferretti, S.; Bucchi, L.
Highlights: Growing difficulties in calculating the proportional incidence of interval breast cancers are emerging in screening programmes. In an Italian regional programme, the proportional incidence of 1st- and 2nd-year interval cancers was 0.16 and 0.37 Although these results are acceptable, their comparability with literature data and with standards is problematic The criteria and methods used to estimate mammography sensitivity need to be revised and standardized